Food systems emissions in Kenya and their reduction potential: A country profile - Martius, C.; Guérin, L.; Pingault, N.; Mwambo, F.M.; Wassmann, R.; Cramer, Laura K.; Shikuku, Kelvin Mashisia (CIFOR-ICRAF, 2023)
Kenya ́s food system emissions remained stable in absolute level over the past decade (2010-2020) at around 63 MtCO2 eq. Building a large forest-related carbon sink has contributed in curbing emissions significantly between 2010 and 2020. So far, the largest sources of emission in Kenya’s food system are enteric fermentation (56% of total emissions), manure left on pasture (24%), and food waste disposal (11%). Altogether, these three categories account for 91% of all food system emissions.